La Geografía en la Escuela Superior del Magisterio (1909-1932) - Rodríguez Esteban, José Antonio (Ería, 1997)
RESUMEN Desde la creación en 1909 de la Escuela Superior del Magisterio, R, Beltrán y Rózpide, en unión con otros profesores como L. de Hoyos y V. Vera, puso en marcha un primer intento de investigación en Geografía humana mediante la realización por los alumnos de monografías territoriales, con el fin último de acopiar materiales para la elaboración de una Geografía humana de España. Se posibilitó así la incorporación y la divulgación de las propuestas de la Geografía humana europea y norteamericana y la aplicación de nuevos métodos de enseñanza en la Geografía española. RÉSUMÉ La géographie dans l'École Normale Supérieur (1909-1932).-L'École Norma1e Supérieur est crée en Espagne en 1909, ce qui a fait possible la création d'une nouvelle chaire de géographie universitaire, occupée par R. Beltrán y Rózpide. C'est Beltrán, en union d'autres professeurs, dont L. de Hoyos et V. Vera, qui ont mis en place une première tentative de recherche en géographie humaine au moyen de monographies territoriales menées à bout par les étudiants. L'objetif était de réunir les matériaux nécessaires pour arriver à produire une géographie humaine de l'Espagne. Ceci a permis d'introduire dans la géographie espagnole les principes de la géographie humaine européene et de l' Amerique du Nord ainsi que de nouvelles méthodes d'enseignement. ABSTRACT The Geography in the Higher School of Educatión (1909-1932).- The starting out of the Higher School of Educatión en 1909 made it possible the stablisment of a second tenure teaching position in the discipline of Geography at the University. To this position was appointed R. Beltrán y Rózpide who, in conjunction with other professors, as L. de Hoyos and V. Vera, embarked in the very first attempt of research in the field of Human Geography by means of the active participation of the students in the writing of regional studies. Following the France example, the aim was to collect data in order to lay out the Peninsular Human Geography. By doing so, the assimilation and spreding out of the proposals advocated by both fue European and NorthAmericán Schools of Human Geography as well as the employement of the new educational methods in the Spanish School, were facilitated. Palabras clave / Mots clé / Key words Escuela Superior del Magisterio, Historia de la Geografía española, Geografía moderna, Geografía humana, monografías de aldea, enseñanza de la Geografía. École Normale Supérieur, Histoire de la Géographie espagnole, Géographie moderne, Géographie humaine, monographies territoriales. enseignement de la Géographie. Higher School of Education, History of Spanish Geography, modern Geography, human Geography, regional studies, Geographical teaching.